Sistem Kendali Suhu Greenhouse Berbasis Arduino dengan Metode Histeresis dan Override Kelembaban Tanah - Iin Yunita Sari; Adi Wibowo (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2025)
This study develops an automatic temperature control system for a mustard plant greenhouse in Madukoro Village using an Arduino-based controller implementing hysteresis temperature control and a soil-moisture override mechanism. The system integrates a DHT11 temperature–humidity sensor, an analog soil moisture sensor, an exhaust fan, and an active-LOW relay–driven sprinkler valve. The novelty of this research lies in the combined logic of a 27°C–26°C temperature hysteresis and an override mechanism that forces cooling to remain active when the soil is critically dry, even when the ambient temperature has not yet exceeded the 30°C upper threshold. The system was tested five times under varying environmental conditions. Experimental results show that the system successfully maintains greenhouse temperature within the 26°C–28°C range, reduces relay switching frequency by 86%, and significantly improves environmental stability. The test tables and temperature trend graphs demonstrate a consistent and adaptive system response to changes in both air temperature and soil moisture levels.